RASIO HUBUNGAN NILAI DAYA DUKUNG TIANG PANCANG BERDASARKAN PENGUJIAN SONDIR, KALENDERING DAN TES PDA PADA JEMBATAN PELAWA KABUPATEN PARIGI MOUTONG - Gunawan, Muhammad; Oktaviana, Ida Sri; B., Arifin (Jurusan Teknik Sipil Universitas Tadulako, 2014)
Bearing capacity of pile foundation bearing capacity is influenced by several factors, such as the amount of applied loads and non-homogeneous soil characteristics. To determine the bearing capacity of single pile foundation the static method is used on the basis of CPT data and dynamic methods based on dynamic pile and PDA tests. Pile foundations of the Pelawa bridge used in this study are located in the District of Parigi - Moutong. The study of literatures and secondary data such as the data of driven pile equipment, driven piles , CPT, dynamic pile tests, and PDA tests are used for analyzing the pile bearing capacity . Meyerhof method, Aoki de Alencar, LCPC, Price and Waldre, and Schmertmann are used to determine the bearing capacity of pile based on sondir (CPT) data. The dynamic pile tests data are used to calculate the bearing capacity of the piles by using methods of Hiley, Olsen and Flaate , Enginering News Record (ENR) , Janbu Mansur and Hunter , and AASHTO . The results show that the lowest dan the highest of the ultimate bearing capacities for static methods (CPT data) are 114.096 tons (Aoki De Alencar) and 305.479 tons (Schmertmann) respectively. Kalendering method (dynamic pile data) show that the lowest value of 284.22 tons were obtained from equation given by Hiley and the highest 1450.26 tons were obtained from equation given by Janbu.The range of 171.2 tons - 174.5 tons were given for PDA test data. The ratio between CPT to PDAs results that are closest to the value of 1 which is 0.938 is the value that obtained from Meyerhof’s equation, while the ratio between dynamic method (kalendering) to PDAs results that are closest to the value of 1 which is 1,660 is the value that obtained from Hiley equation Keywords: single pile bearing capacity, CPT, dynamic pile test, PDA test